A retrospective review of the long-term outcomes of online adaptive radiation therapy and conventional radiation therapy for muscle invasive bladder cancer. (September 2021) - Yeh, Janice; Bressel, Mathias; Tai, Keen Hun; Kron, Tomas; Foroudi, Farshad
Highlights: Risks with tight adaptive RT margins. Cancer control may be poorer if margins tight. Prospective studies required. Abstract: Background and Purpose: To report long-term outcomes of online image-guided (IG) adaptive radiation therapy (aRT) versus conventional IG radiation therapy (cRT) for bladder preservation in muscle-invasive bladder cancer (MIBC). Materials and Methods: A retrospective review of patients with histologically proven MIBC who were prescribed radical intent radiation therapy (RT) following trans-urethral resection of bladder tumour (TURBT) was conducted. There were three groups based on their RT treatment modality: conventional RT (cRT), margin 5 mm adaptive RT (aRT5mm) and margin 7 mm adaptive RT (aRT7mm). Results: 171 patients were included in this study, with median age of 79.4 years (41–90). Approximately half of all patients received concurrent chemotherapy. N = 57 underwent cRT, n = 39 underwent aRT5mm, and n = 75 underwent aRT7mm. Response evaluable patients in all three groups (n = 133) had high rates of complete response (CR, 83%) on first post-RT cystoscopy with no significant differences between the groups. At a median follow-up of 54 months, the 5-year freedom from muscle-invasive failure survival (FFMIFS) in the cRT, aRT5mm, and aRT7mm groups were 75%, 59%, and 98%, respectively. The estimated cancer specific survival (CSS) at 5 years were 60%, 30%, and 59%, respectively. The estimated overall survival (OS) at 5 years were 43%, 26%, and 38%, respectively. The incidence of late grade 3 or 4 toxicity was n = 5 in aRT5mm, n = 2 in cRT group, and n = 1 in aRT7mm. Conclusion: IG aRT with 7 mm expansion for MIBC provides higher rates of FFMIFS, similar 5-year CSS and OS, as well as toxicity outcomes when compared to cRT. aRT with 5 mm expansion with this RT protocol is not recommended for treatment.